Lifestyle and risk of developing myopia in school children in Chongqing, China - Li, Ruili; Zhang, Jing; Zhang, Yong; Tang, Wensheng; Ao, Dan; He, Li; Yang, Kun; Qi, Xiaoya (Frontiers in Medicine, 2024)
This study aims to investigate the influence of lifestyles on myopia in schoolchildren in Chongqing, China. This cross-sectional study was conducted on primary and junior high school graduates in Chongqing City, China. Students who came to the assigned hospital for the physical examination of their upgrade school enrollment were recruited. In addition to regular examination and eye-using questionnaire, visual acuity and non-cycloplegic autorefraction were measured. Of all 1806 eligible students, 1623 students (89.87%) were included in the analysis. The prevalence of myopia in elementary and junior middle school graduates was 73.1% and 81.8%, respectively. According to the multivariate logistic regression analysis, 1 hour more homework (OR =1.272, p=0.032), attending out-school courses (OR =1.973, P=0.006), frequently checking of eyes (OR =1.337, P=0.015) and using eye-protecting lamp (OR =2.528, P<0.001) were more likely to be associated with myopia (P < 0.05). while 1 hour more outdoor activity in weekday (OR =0.811, P=0.033) and weekend (OR =0.796, P=0.034) were less likely to have myopia. The current prevalence of myopia among elementary and junior high school students in Chongqing is high. Academic pressures, bad habits of using eyes, and limited time for outdoor activity mainly contribute to the epidemic of myopia.Various policies in and out of schools related to reducing academic pressures, increasing outdoor activities, and improving eye habits may help control the prevalence of myopia in teenagers.